THE ROLE OF THE PRINCIPAL IN IMPROVING THE PERFORMANCE OF EDUCATORS AT SMP NEGERI 1 SAWIT SEBERANG - Agus Setiawan Tanjung; Adam; Walid Musthafa Sembiring (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the role of the principal in improving the performance of educators at SMP Negeri 1 Sawit Seberang and to identify the factors that hinder its implementation. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation. The informants in this study consisted of the principal, vice principal, and several teachers directly involved in the learning process. The results indicate that the principal plays roles as an educator, manager, administrator, supervisor, leader, innovator, and motivator in efforts to enhance teachers’ performance. These roles are manifested through routine guidance, classroom supervision, motivational support, evaluation meetings, and the facilitation of training activities and professional development programs for teachers. However, several inhibiting factors were identified, including teachers approaching retirement age, limited mastery of instructional technology, economic issues affecting work motivation, and the geographical distance between teachers’ residences and the school.